ANALISIS KINERJA TURBIN UAP BERDASARKAN PERFORMANCE TEST PLTU PT. INDOCEMENT P-12 TARJUN - Riyki Apriandi; Aqli Mursadin (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2016)
This study aims to determine the performance of steam turbine PT. Indocement Tarjun Plant 12 by comparing the results of data obtained during each performance test in 1999, 2016, 2017, and 2018. This research data is taken from the control room of PT. Indocement Tarjun, variable data obtained in the form of load, main inlet steam temperature, main inlet steam pressure, HP heater feed outlet temperature, HP heater feed outlet pressure, main steam flow, and turbine by pass flow. The data is processed to get the turbine heat rate and the efficiency per time of each performance test and then averaging the data results over time, then comparing the turbine heat rate and the average efficiency of each performance test. The calculation of turbine heat rate using heat & mass balance method, turbine efficiency is obtained by comparing the energy of 1 kW with turbine heat rate and multiplying 100%. The result of the average heat turbine calculation per performance test ie August 1999 is 2.546, April 2016 2,537, June 2017 2.56, and May 2018 2.67. The average value of turbine efficiency in August 1999 was 39.30%, April 2016 39.43%, June 2017 39.07%, May 2018 37.46%. Turbine power plant performance of PT Indocement Tarjun Plant 12 decreased from 1999 to 2018 by 1.84%.